Troubled times: sustainable development and governance in the age of extremes (Sustainable Development Policy Institute, 2006)
section 1. Globalization and rural livelihoods -- section 2. Farmers' rights and natural resource management -- section 3. Environmental governance -- section 4. Trade and environment -- section 5. Politics, peace and society -- section 6. Health care finance -- section 7. History and culture -- section 8. Literature